Hiperconsumo: comunicação, condicionamento e compras das décadas de decisão à década de descontrole - Colombo, Caio Prisco da Silva Telles Nunes Ranieri (2012)
This Doctoral Thesis in Communication and Semiotics deals with the excessive consumption of goods in the contemporary world and the central role of commercial communication in the construction, development and maintenance of consumption-oriented societies. The phenomena of consumerism and hyper-consumerism are fruits of commercial communication and depend on it, mostly or fully, to continue to exist. Studying Consump-tion is extremely important to understand Man, Culture and the local and global socio-economic dynamics in the capitalist system. This Thesis arose from the author s concern with the excessive consumption of goods in the world and the alarming increase in the number of consumerist and hyper-consumerist individuals every-where. The problem of this Thesis is: How capitalist enterprises have been using Communication, in its commer-cial form, since the second half of the nineteenth century, to achieve their goals of Profit? The hypothesis is: The capitalist enterprises have been using Communication, in its commercial form, since the second half of the nine-teenth century as a tool to build, develop and maintain societies oriented towards the excessive consumption of goods. Consumption is a complex phenomenon and has relations, directly and indirectly, with others of great complexity. To grasp this complexity we chose to use Systemic Semiotics as key for the decoding and under-standing of what has motivated and guided human life in recent times. The main theorists present in this text are Gilles Lipovetsky, Guy Debord, István Mészáros, Jean Baudrillard, Pierre Bourdieu, Theodor Adorno and Zygmunt Bauman. The excessive consumption of goods destroys the human psyche, Society and Environment and is only possible operationally feasible and publicly acceptable due to the planned and full use (in fact, plenipotentiary use) of commercial communication as a tool for the construction, development and mainte-nance of an artificial reality, based, essentially, on Desire, in Individualism and Hedonism, all hypertrophied, and constantly fanned by the Media in the service of Capital. Through a systemic semiotic analysis, beginning in 1850 and ending on the last day of 2009, it is possible to understand the general movements of Industry, Com-merce and Advertising and the culture built, legitimized and reinforced by these three agents over time which resulted in consumerism (the overstatement in purchases) and, more recently, in hyper-consumerism (the disease of addiction in purchases)